Experimental investigation of neutron spectra generated in a copper target by 10 MeV protons - Yegorov, A.M.; Migalenja, V.Ja.; Nagaychenko, V.I.; Sotnikov, V.V.; Voronko, V.A.; Zhuk, V.V. (Вопросы атомной науки и техники, 2004)
The intensity and energy spectra of neutron radiation arising as a result of interaction of the accelerated proton beam with a copper target were measured at a proton energy of 10 MeV. The neutron spectrum was measured using two different techniques: i) with pulse-shape discrimination of gamma-background, and ii) by activation detectors.
The neutron yield from the (p,n) reaction was estimated. For the copper target, the neutron yield per accelerated proton of energy 10 MeV was (3.5 ± 1.0)⋅10⁻³. Проведено вимір енергетичних спектрів і інтенсивності нейтронного випромінювання, генеруемого в
мідній мішені пучком протонів з енергією 10 МеВ. Спектри нейтронів вимірювалися за допомогою двох
різних методик: з дискримінацією гамма-фону за формою імпульсу, а також із застосуванням активаційних
детекторів. Визначено вихід нейтронів з мідної мішені - (3.5±1.0)·10⁻³ на один прискорений протон з
енергією 10 МеВ. Проведено измерение энергетических спектров и интенсивности нейтронного излучения, генерируемого
в медной мишени пучком протонов с энергией 10 МэВ. Спектры нейтронов измерены с помощью двух различных методик: с дискриминацией гамма-фона по форме импульса, а также с применением активационных
детекторов. Определен выход нейтронов из медной мишени – (3.5±1.0)·10⁻³ на один ускоренный протон с
энергией 10 МэВ.